아버지의 정서적 자녀가치에 따른 양육행동이 취학 전후 남녀 아동의 학습준비도와 실행기능에 미치는 영향 - 박지은(Ji Eun Park); 이주아(Joo Ah Lee); 정혜민(Hye Min Chung); 최나야(Naya Choi) (Korean Journal of child studies, 2018)
Objectives: The purpose of this study was to examine successful adaptation of first graders to elementary school by analyzing the relationships among fathers’ emotional valuation of children and parenting behaviors and children’s school readiness and executive function, and to identify gender differences in the pathways. Methods: Data were drawn from waves 6-8 of the Panel Study of Korean Children(PSKC). Participants were 987 fathers and their children. Data were analyzed using structural equation modeling and multiple group analysis with SPSS 22.0 and AMOS 21.0. Results: First, fathers’ emotional valuation of children had a significant effect on both warm and controlled parenting behaviors, and parenting behaviors completely mediated the effects between fathers’ emotional valuation and children’s school readiness and executive function. Furthermore, the results of multiple group analysis revealed that some path weights appeared differently by gender. For boys, fathers’ emotional valuation had a significant effect on children’s school readiness through parenting behaviors; however, there was no effect on executive function. For girls, emotional valuation completely mediated the effects of children’s school readiness and executive function through both parenting behaviors. Conclusion: The implications of these findings provide specific, basic information for parent education and instruction regarding the perception and performance of the father's role emphasizing its the importance in the family. KCI Citation Count: 6